Early Detection of Hypertension (EDH) Skoring dalam Memprediksi Kejadian Hipertensi pada Usia Produktif - Nurpratiwi Nurpratiwi; Debby Hatmalyakin; Mimi Amaludin; Uti Rusdian Hidayat; Ali Akbar; Defa Arisandi; Fauzan Alfikrie (Fakultas Ilmu Kesehatan, 2023)
Hypertension is a disease that cannot be cured but can be managed well to maintain optimal patient conditions. The number of people with hypertension is increasing. In addition, hypertension is called a